The Vascularized Fibular Graft in the Pediatric Upper Extremity: A Durable, Biological Solution to Large Oncologic Defects. (7th October 2013) - Zelenski, Nicki; Brigman, Brian E.; Levin, L. Scott; Erdmann, Detlev; Eward, William C.
Abstract : Skeletal reconstruction after large tumor resection is challenging. The free vascularized fibular graft (FVFG) offers the potential for rapid autograft incorporation as well as growing physeal transfer in pediatric patients. We retrospectively reviewed eleven pediatric patients treated with FVFG reconstructions of the upper extremity after tumor resection. Eight male and three female patients were identified, including four who underwent epiphyseal transfer. All eleven patients retained a functional salvaged limb. Nonunion and graft fracture were the most common complications relating to graft site (27%). Peroneal nerve palsy occurred in 4/11 patients, all of whom received epiphyseal transfer. Patients receiving epiphyseal transplant had a mean annual growth of 1.7 cm/year. Mean graft hypertrophy index increased by more than 10% in all cases. Although a high complication rate may be anticipated, the free vascularized fibula may be used to reconstruct large skeletal defects in the pediatric upper extremity after oncologic resection. Transferring the vascularized physis is a viable option when longitudinal growth is desired.